Granting Of Civil Use Rights In the IKN In Presidential Regulation Number 75 Of 2024 Is Reviewed Through the Dusturiyah Siyasah - zawil zawil; Chairul Fahmi; T. Surya Reza (Journal of Innovative and Creativity, 2025)
The Capital City of the Archipelago is a major project of the government to move the capital city of Indonesia with the aim of making it a sustainable city in the world, as a driver of the Indonesian economy and a symbol of national identity and a form of Indonesian diversity, many new regulations have been formed by the government to accommodate the implementation of IKN development, one of which is Presidential Regulation Number 75 of 2024 concerning the Acceleration of the Development of the Capital City of the Archipelago which in one of its material contents there is a regulation on the period of control of Cultivation Rights (HGU) which is relatively very long compared to the arrangements in other laws and regulations. This research was conducted to determine the validity of the HGU period in Presidential Regulation Number 75 of 2024 based on Indonesian regulatory law and the perspective of siyasah dusturiyah. The research method is qualitative with analysis of problems by literature study from primary and secondary data sources in the form of reading materials. The results of the research obtained state that based on the relationship of super and sub-ordination and special law (specialis), the HGU time in IKN contained in Presidential Decree No. 75 of 2024 does not conflict with the HGU contained in other laws and regulations. siayasah dusturiyah review in the context of legislation provides flexibility for the state in shaping the law provided that it aims to benefit and is in line with sharia